Are categories’ cores more isomorphic than their peripheries? - Cai, Yingying; De Smet, Hendrik (Frontiers in Communication, 2024)
Isomorphism holds that, ideally, a single meaning is expressed by a single form. However, despite long-standing support, the theoretical viability of the isomorphic principle has been called into question. There is widespread recognition that the coexistence of (near-) synonymous expressions—variation—is actually very common in language. In this study, we explore a possible path toward reconciling the theoretical notion of isomorphism with the observable fact of variation. To this end, we adopt an analogy to tool use inspired by Zipf (1949). Tools largely monopolize their core functional domains (e.g., for cutting, knives are overwhelmingly preferred over screwdrivers) but compete over more peripheral functions (for puncturing, knives and screwdrivers have more equal chances of selection). In the same way, we hypothesize forms can code a prototypically organized network of senses, whereby they largely monopolize the core but are more likely to come into competition with other forms in the periphery. To test this hypothesis, a case study is conducted on variation in the use of two prepositions: at and with. For each, a semantic core and periphery are established. Using a corpus consisting of parallel translations of the same source text, it is then tested whether translators are more likely to converge on the same preposition to express one of that preposition’s core senses than to express one of its peripheral senses. This is the pattern one would expect if isomorphic pressure is stronger for semantic cores than for peripheries. The results are promising but inconclusive. They confirm that the sense most prone to competition is arguably the most peripheral but also reveal a surprisingly high level of competition for the spatial core use of at.